Advances in physiological mechanisms of selenium to improve heavy metal stress tolerance in plants. (21st July 2022) - Lai, X.; Yang, X.; Rao, S.; Zhu, Z.; Cong, X.; Ye, J.; Zhang, W.; Liao, Y.; Cheng, S.; Xu, F.
ABSTRACT: Selenium (Se) is a metalloid mineral nutrient for human and animal health. Plants are the main foodstuff source of the Se intake of humans. For plants, the addition of an appropriate amount of Se could promotes growth and development, and improves the tolerance to environmental stress, especially stress from some of heavy metals (HM) stress, such as cadmium (Cd) and mercury (Hg). This paper mainly reviews and summarizes the physiological mechanism of Se in enhancing HM stress tolerance in plants. The antagonistic effect of Se on HM is a comprehensive effect that includes many physiological mechanisms. Se can promote the removal of excessive reactive oxygen species and reduce the oxidative damage of plant cells under HM elements stress. Se participates in the regulation of the transportation and distribution of HM ions in plants, and alleviates the damage caused by of HM stress. Moreover, Se combine with HM elements to form Se‐HM complexes and promote the production of phytochelatins (PCs), thereby reducing the accumulation of HM ions in plants. Overall, Se plays an important role in plant response to HM stress, but current studies mainly focus on physiological mechanism, and further in‐depth study on the molecular mechanism is essential to confirm the participation of Se in plant response to environmental stress. This review helps to comprehensively understand the physiological mechanism of Se in plant tolerance against to HM stress of plants, and provides important theoretical support for the practical application of Se in environmental remediation and agricultural development. Abstract : Selenium (Se) promote the removal of excessive reactive oxygen species (ROS) and participates in the regulation of the transportation and distribution of heavy metals (HM) ions in plants alleviates the damage under HM elements stress. Se combine with HM elements to form Se‐HM complexes and promote the production of phytochelatins (PCs), thereby reducing the accumulation of HM ions in plants.